Administrative Management Indah Jaya Tamiang Women Farmers Group - Fara Fitriyani (EQUATOR SINAR AKADEMIA, 2023)
Community service is carried out at the Indah Jaya Tamiang Farming Women's Group (KWT), Tamiang Village, Gunung Kaler District, Tangerang Regency. Farming Women's Group (KWT) is one of the women's empowerment programs in increasing the role of women towards healthy, prosperous families through the utilization of local resource potential. The purpose of this activity is to improve the administrative abilities of women farmer groups so that they can function optimally because the Indah Jaya Tamiang Farming Women Group (KWT) does not yet have good group administration and managerial skills. The method used in this activity is administrative training for the management of the Indah Jaya Tamiang Farming Women's Group (KWT).